Particularities long-term storage of light oil products - Матвеева, О. Л.; Столінець, С. Л. (Proceedings of National Aviation University (archive), 2021)
The problem of preservation of quality of propellants is reviewed at their long-term storage. At use of the technological analysis the processes are determined, which one take place at storage of propellants and degree of their influencing on quality of propellants.